Interpretasi Komparatif Ta’wīl Sufi Abū Ḥāmid al-Ghazālī dan Ibn ‘Arabī terhadap Ayat-ayat al-Qur’ān - Wahyudi Wahyudi (Islamika Inside: Jurnal Keislaman dan Humaniora, 2018)
This article presents a study of ta’wīl promulgated by two prominent Sufis, namely Abū Ḥāmid al-Ghazālī and Ibn ‘Arabī. Although both use the ta’wīl method of explaining the Qur’anic verses, they are different in terms of “the school” they embrace to. When al-Ghazali belongs to the Sunni Sufi category, Ibn ‘Arabī is a representation of the Naẓarī Falsafī Sufi. In their ta’wīl both Sufis employ symbols as a medium to understanding. In al-Ghazālī’s perspective, symbols are the most appropriate method to explain the meaning obtained through kashf. As for Ibn ‘Arabī, the symbol is a method of solving and breaking down the ultimate reality associated with the basic concepts of truth, nature, and man. The symbolic language framework can be known only by certain people who have a clean and pure heart. In interpreting the Qur’ān, Ibn ‘Arabī and al-Ghazālī belong to the category of those who use symbolism interpretation approach; interpreting the Qur’anic verses which are incompatible with the extrinsic meaning of the texts but with their abstract symbols.